“What Is the ROI on That?”: Examining the Lack of Transition Support for Collegiate Athletes - Corr, Chris; Stokowski, Sarah; Berg, Brennan K.; Gearity, Brian; Sabin, Eric (Journal of Organizational Psychology, 2024)
While athletic role engulfment is positively correlated to athletic success, collegiate athletes also experience harmful effects from this role. As the socialization process to develop a salient athletic identity initially takes years, collegiate athletes typically face various challenges transitioning out of their athletic role. Although working within the contested and problematic context of intercollegiate athletics, athletic development staff are, ostensibly, employed to assist in the holistic development of collegiate athletes and occupy an integral role in mitigating athletes’ transitions and athletic role engulfment. Accordingly, the present study sought to examine the experiences and programmatic elements currently utilized by athletic development staff. Through in-depth interviews with 10 senior athletic development staff members at nine Atlantic Coast Conference member institutions, findings illustrate the difficulties in attempting to combat athletic role engulfment due to contradictory logic between intra-institutional members. We conceptualize that such competing institutional logic serves as the primary detriment of collegiate athletes’ preparedness for post-athletic transition.